Ocular Manifestations Leading to a Diagnosis of Joubert Syndrome Related Disorder - Jain, Divya; Ravishankar, Venkateshwar (Nepalese Journal of Ophthalmology, 2022)
Introduction: Joubert syndrome is an inherited disorder of rare occurrence usually presenting as developmental delay, hypotonia, hyperpnea and ataxia. The diagnosis is confirmed by characteristic findings in neuroimaging. Involvement of ocular, renal and hepatic systems can be present. Joubert syndrome presenting first to an ophthalmologist is very uncommon. Case: A twenty-one-year female, with history of delayed milestones, infantile hemiplegia with hearing and visual impairment was referred for visual assessment. On systemic examination, ataxic gait was present. CT head showed hypoplasia of postero-inferior portion of vermis with communication between 4th ventricle and cisterna magna with variable degree of cerebellar dysgenesis. The neurological, ophthalmological and radiological findings of this patient were consistent with Joubert syndrome related disorder. Conclusion: We hereby report a case of Joubert syndrome related disorder with ocular involvement which after correlation with neurological findings and neuroimaging led us to the diagnosis of this rare disorder. The renal and hepatic functions in these patients need to be monitored.